DESAIN APLIKASI B2B SISTEM MANAJEMEN PERGUDANGAN DALAM PENUNJANG KEPUTUSAN BISNIS - Ahmad Roihan; Abdul Hamid Arribathi; Nurussaadah Nurussaadah (CCIT Journal, 2019)
Warehousing data processing based on products entering and leaving the expedition in Super Tata Raya Steel companies has several obstacles in the delivery of information. Data management carried out by the warehouse section of the company is still manual, especially in terms of the recording and bookkeeping system of product receipts and shipments. In dealing with these problems, this research uses several stages among observation, analysis, planning and design methods with object-oriented approaches that use UML (Unified Modeling Language). So that this research can develop it into a system design in the form of web-based applications using the PHP and MySQL programming languages. The existence of a new system aims to support business-to-business between the expedition services with the company and to reduce the occurrence of errors during warehousing data processing then data management becomes faster and more accurate so that the resulting report is in accordance with the existing data. Therefore, this research can be used as a support for the leadership's decision in determining business patterns in the warehousing sector, so management of company services become effective and efficient